"A Wonderful World?": C&S's Georgia Plan, Urban Renewal, and Historic Preservation in Savannah, Augusta, and Macon. - SOUTHER, J. MARK (Georgia Historical Quarterly, 2025)
The article focuses on the Georgia Plan initiated by Citizens and Southern National Bank (C&S) under president Mills B. Lane Jr., which aimed to address urban blight and poverty through a series of community revitalization efforts in cities like Savannah, Augusta, and Macon during the late 1960s. The plan included initiatives such as the "Spring Cleaning '68" campaign, which involved extensive cleanup efforts and the provision of loans for housing rehabilitation and business development, particularly targeting African American communities. While the program garnered initial support and aimed to foster community engagement and historic preservation, it ultimately faced criticism for its limited impact on systemic issues of poverty and gentrification, leading to mixed outcomes in the targeted neighborhoods. The Georgia Plan serves as a case study of the complexities surrounding urban renewal and the challenges of achieving meaningful change through private sector initiatives.